Parallel and large‐scale antitumor investigation using stable chemical gradient and heterotypic three‐dimensional tumor coculture in a multi‐layered microfluidic device. Issue 10 (14th July 2021) - Liu, Wenming; Hu, Rui; Han, Kai; Sun, Meilin; Liu, Dan; Zhang, Jinwei; Wang, Jinyi
Abstract: Background: Cancer has been responsible for a large number of human deaths in the 21st century. Establishing a controllable, biomimetic, and large‐scale analytical platform to investigate the tumor‐associated pathophysiological and preclinical events, such as oncogenesis and chemotherapy, is necessary. Methods and Results: This study presents antitumor investigation in a parallel, large‐scale, and tissue‐mimicking manner based on well‐constructed chemical gradients and heterotypic three‐dimensional (3D) tumor cocultures using a multifunction‐integrated device. The integrated microfluidic device was engineered to produce a controllable and steady chemical gradient by manipulative optimization. Array‐like and size‐homogeneous production of heterotypic 3D tumor cocultures with in vivo‐like features, including similar tumor‐stromal composition and functional phenotypic gradients of metabolic activity and viability, was successfully established. Furthermore, temporal, parallel, and high‐throughput analyses of tumor behaviors in different antitumor stimulations were performed in a device based on the integrated operations involving gradient generation and coculture. Conclusion: This achievement holds great potential for applications in the establishment of multifunctional tumor platforms to perform tissue‐biomimetic neoplastic research and therapy assessment in the fields of oncology, bioengineering, and drug discovery. Graphical Abstract and Lay Summary: Establishing a controllable, biomimetic, and high throughput analytical platform to investigate tumor‐associated pathophysiological and preclinical events such as oncogenesis and chemotherapy is necessary. A parallel and large‐scale antitumor evaluation using heterotypic 3D tumors stimulated with a drug concentration gradient in a single integrated microfluidic system with multifunctional composition is presented. The system allows stable and long‐term generation of chemical gradients and array‐like production of tumors with tissue‐biomimetic phenotypes in a large‐scale and size‐uniform manner. Multi‐concentration chemotherapy is accomplished with high throughput in a single device.